Erosive pustular dermatosis of the scalp: a multicentre study. (9th February 2020) - Starace, M.; Iorizzo, M.; Trüeb, R.M.; Piccolo, V.; Argenziano, G.; Camacho, F.M.; Gallyamova, Y.; Rudnicka, L.; Umbert, I.; Lyakhovitsky, A.; Vañó‐Galván, S.; Goren, A.; et al.
Abstract: Background: Erosive pustular dermatosis of the scalp (EPDS) is characterized by crusted erosions or superficial ulcerations that lead to scarring alopecia. Objectives and Methods: We performed a multicentre retrospective clinical study including 56 patients (29 females and 27 males, mean age 62.7) with a confirmed EPDS in order to describe epidemiology, clinical findings and therapeutic choices of this disease. Results: Mechanical/chemical trauma was reported in 28.6%, a previous infection in 10.7%, a previous cryotherapy in 5.4% androgenetic alopecia in 48.2% and severe actinic damage in 25%. Trichoscopy showed absence of follicular ostia, tufted and broken hair, crusts, serous exudate, dilated vessels, pustules and hyperkeratosis. Histopathology revealed three different features, depending on the disease duration. The most prescribed therapy was topical steroids (62.5%), followed by the combination of topical steroids and topical tacrolimus (8.9%), systemic steroids (7.1%) and topical tacrolimus (5.4%). A reduction of inflammatory signs was observed in 28 patients (50%) treated with topical steroids and in all three patients treated with topical tacrolimus. Conclusion: The relatively high number of patients collected allowed us to identify a better diagnostic approach, using trichoscopy and a more effective therapeutic strategy, with high‐potency steroids or tacrolimus, which should be considered as first‐line treatment.